A Hypothesis of the Interaction of the Nitrergic and Serotonergic Systems in Aggressive Behavior Induced by Exposure to Lead - Martínez-Lazcano, Juan Carlos; López-Quiroz, Alfredo; Alcantar-Almaraz, Rocío; Montes, Sergio; Sánchez-Mendoza, Alicia; Alcaraz-Zubeldia, Mireya; Tristán-López, Luis Antonio; Sánchez-Hernández, Beatriz Eugenia; Morales-Martínez, Adriana; Ríos, Camilo; Pérez-Severiano, Francisca (Frontiers in Behavioral Neuroscience, 2018)
The effects caused by exposure to lead (Pb) are still considered as a relevant health risk despite public policies aimed to restricting the use of this element. The toxicity limit in the blood (10 µg/dL, established by the Center for Disease Control and Prevention) has been insufficient to prevent adverse effects and even lower values have been related to neurobehavioral dysfunctions in children. Currently, there is not a safe limit of exposure to Pb. A large body of evidence points to environmental pollutant exposure as the cause of predisposition to violent behavior, among others. Considering the evidence by our group and others, we propose that Pb exposure induces alterations in the brain vasculature, specifically in nitric oxide synthases, affecting in turn the serotonergic system and leading to heightened aggressive behavior in the exposed individuals. This review describes the consequences of Pb exposure on the nitrergic and serotonergic systems as well as its relationship with aggressive behavior. In addition, it summarizes the available therapy to prevent damage in gestation and among infants.